Characterization and performance evaluation of epoxy-based plastic scintillators for gamma ray detection - Pancoko, Marliyadi; Nuri, Hafni L.; Prasetyo, Andjar; Manaf, Azwar; Jami, Abdul; Yanto, Ausatha R.; Kasmudin,; Utomo,; Djokorayono, Rony; Suntoro, Achmad (Frontiers in Physics, 2024)
This research investigates the fabrication and analysis of plastic scintillators using an epoxy matrix. Plastic scintillators are widely used in radiation detection because of their low cost, ease of fabrication, resistance to moisture, and rapid decay time. The production process involved dissolving primary and secondary dopants, p-terphenyl (p-TP) and 1,4-bis[2-(phenyloxazolyl)]-benzene (POPOP) , respectively, into a low-viscosity of cycloaliphatic amine as hardener B, which was then combined with Bisphenol-A diglycidyl ether as epoxy A. The ratio of primary and secondary dopants was varied in the experiment.The resulting scintillators were characterized using Fourier Transform Infrared Spectroscopy (FTIR) to analyze the functional groups that constitute the epoxy before and after curing. The morphology of the scintillator sample was evaluated using SEM and The thermal properties were evaluated with differential scanning calorimetry (DSC). The optical properties of the scintillator were studied using a UV-Vis Spectrophotometer and a Fluorescence Spectrophotometer. The performance of the scintillator in detecting gamma rays was evaluated using a module comprising a Photomultiplier Tube (PMT) and a Multichannel Analyzer (MCA) with sources of gamma Cesium 137. The results showed that epoxy-based scintillators can provide a detective response to gamma rays. This study demonstrates the potential of epoxy-based plastic scintillators for use in radiation detection.